Information, branding, certification, and consumer willingness to pay for high-iron pearl millet: Evidence from experimental auctions in Maharashtra, India - Birol, Ekin; Karandikar, Bhushana; Rampal, Jeevant; Banerji, Abhijit (International Food Policy Research Institute, 2015)
In this paper we use sensory evaluation methods adopted from food science literature and the Becker-DeGroot-Marschak mechanism adopted from economic valuation literature to estimate consumer demand for biofortified high-iron pearl millet (HIPM) in Maharashtra, India. Unlike biofortification with provitamin A, biofortification with minerals, such as iron and zinc, does not change the color or the appearance of the biofortified crop. Therefore, we test the impact of both nutrition information, and branding and certification, as well as the nature of the brand and of the certifying authority (state level versus international), on consumer demand for HIPM. We find that even in the absence of nutrition information, consumers assign a small but significant premium to the HIPM variety relative to the local variety. This is consistent with consumers’ more favorable rating of the sensory characteristics of the high-iron variety. Nutrition information on the health benefits of HIPM increases this premium substantially, and regression analysis reveals that consumers prefer international branding and international certification authority to their state-level counterparts.